2020
DOI: 10.1111/rda.13761
|View full text |Cite
|
Sign up to set email alerts
|

Serum kisspeptin: New possible biomarker for sexual behaviour and sperm concentration in buffalo bulls

Abstract: The study was designed to decipher the inter‐relationship between peripheral hormones (kisspeptin and testosterone), sexual behaviour and seminal variables of Murrah buffalo bulls (n = 134). In this study, we recorded that 13%, 37%, 40%, 6% and 4% Murrah buffalo bulls had reaction time of <30, 31–60, 61–180, 181–300 and >300 s, respectively. Further, it was observed that 4%, 85% and 10% buffalo bulls were sexually aggressive, active and dull, respectively, during semen collection. The courtship behaviour was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…Moreover, on approach to the female, males displaying characteristic aggressive behaviors (ie, uncontrollable, and extremely eager to mount and approach with full vigor) had significantly higher KP levels, compared to dull males (ie, proceeding with a dull expression and longer time to mount). In keeping with earlier rodent evidence ( 273 , 276 ), males with lower KP levels also exhibited incomplete penile erection and protrusion ( 279 ). Hence, these findings suggest that circulating KP levels may offer a novel biomarker for sexual behavior in male domestic animals.…”
Section: Clinical Applications Of Kisspeptinsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, on approach to the female, males displaying characteristic aggressive behaviors (ie, uncontrollable, and extremely eager to mount and approach with full vigor) had significantly higher KP levels, compared to dull males (ie, proceeding with a dull expression and longer time to mount). In keeping with earlier rodent evidence ( 273 , 276 ), males with lower KP levels also exhibited incomplete penile erection and protrusion ( 279 ). Hence, these findings suggest that circulating KP levels may offer a novel biomarker for sexual behavior in male domestic animals.…”
Section: Clinical Applications Of Kisspeptinsupporting
confidence: 88%
“…Moving from rodents to male domestic animals, recent data provide evidence for the relationship between circulating KP levels and sexual behavior in buffalo bulls ( 279 ). In this study, it was observed that KP levels were significantly lower in bulls with longer reaction times (ie, time from exposure to mounting the female).…”
Section: Clinical Applications Of Kisspeptinmentioning
confidence: 99%
“…They also found that 4, 85, and 10% of buffalo bulls were active, sexually aggressive, and dull, respectively, during semen collection. Serum kisspeptin and testosterone possess negative effects on reaction time, sexual aggressiveness, penile erection, and positive effect in spermatogenesis [19]. In another study, the relationship of blood metabolic changes and average daily gain with feed conversion efficiency were assessed in Murrah Heifers (Murrah buffalo) through a machine learning approach [20].…”
Section: Background Of Buffalo Research In the Asian Subcontinentmentioning
confidence: 99%
“…Interestingly, buffalo spermatozoa also possess GPR54 receptors on head, neck and mid‐piece (Hussain et al, 2020) thus supporting that kisspeptin‐10 may reliably be tested during sperm cryopreservation. Moreover, serum kisspeptin‐10 has also been reported to act as a biomarker for better reproductive performance in buffalo bulls (Bhardwaj et al, 2020). Therefore, we hypothesized that in‐vitro supplementation of kisspeptin‐10 in cryodiluent may improve the post‐thaw buffalo sperm structure and function by strengthening its existing antioxidant system.…”
Section: Introductionmentioning
confidence: 99%